Comparison of life history traits of Tanais dulongii (Tanaidacea: Tanaididae) in natural and artificial marine environments of the south-western Atlantic - Rumbold, Carlos Enrique (2015)
Tanaidaceans are small benthic crustaceans with a strictly benthic life cycle and low dispersion rates, so they are good candidates to evaluate the effects of environment over life history strategies and reproductive biology. In this work, we studied two populations of Tanais dulongii (Audouin, 1826) that live in two contrasting habitats in order to determine whether they differ in life history traits. The animals were obtained by systematic sampling in a rocky shore with a lower anthropic impact (La Estafeta: LE) and a polluted area (Mar del Plata harbour: MdP) from March 2011 to March 2012. Seawater temperature and salinity did not differ between sites, but MdP showed more acid and hypoxic conditions than LE. Population density was homogeneous and lower in MdP (ca. 20 ind/100 gr) than that in LE where density varied between 250 and 800 ind/100 gr. Reproductive individuals and juveniles were always present, and both populations showed two main recruitment periods: the first in spring in both populations, and the second in summer in MdP but in autumn–winter in LE. In both populations, sex ratio was strongly female-biased. Juveniles, females and males from LE had larger sizes than that from MdP and reached their sexual differentiation at larger sizes. The estimated lifespan was about 9 and 12 months in MdP and LE, respectively. This study suggests that the differences observed between populations of T. dulongii in life history traits are intimately related to environmental differences in pH and dissolved oxygen between habitats, but should not be discarded a synergistic effect of temperature, organic pollution, food availability and predation pressure.